Routledge philosophy guidebook to Husserl and the Cartesian meditations - Smith, A. D. (Arthur David) (Routledge philosophy guidebooks., 2003)
A comprehensive introduction to Husserlian phenomenology. Smith introduces and assesses the key concepts that arise in the text in a clear and engaging way. A highly accessible introduction to the Cartesian Meditations.